Inventory of Terrestrial Orchids in the Baturraden Botanical Garden of Central Java - Astuti, Sutan Nur Chamida Tri; Aisah, Siti; Kurniawan, Ardyan Pramudya (Journal of Biotechnology and Natural Science, 2022)
Baturraden Botanical Garden located on the slopes of Mount Slamet in the south has a high enough humidity so it is ideal for plant growth, especially orchids. As an ex-situ plant conservation area, the Baturraden Botanical Garden plays an important role in preserving the diversity of orchids in it. The purpose of this study was to find out the types and descriptions of terrestrial orchids in the Baturraden Botanical Garden area of Central Java. The method used in this study is a 400 m line transect method with an inter-point distance of 100 m each and data collection is carried out at 10 m each on the right and left of the line transect.  Hasil research shows that there are 13 species derived from 10 genus of soil orchids. The types that have been found are Goodyera rubicunda (Blume) Lindl., Calanthe pulchra (Blume) Lindl., Spathoglottis plicata Blume, Cryptostylis javanica J.J.Sm., Appendicula alba Blume, Phaius callosus (Blume) Lindl., Lepidogyne longifolia Blume, Tainia elongata J.J.Sm., Goodyera colorata Blume, Malaxis sp. Soland. ex Sw., Goodyera sp. R. Br., Goodyera procera (Ker-Gawl.) Hook., and Plocoglottis sp. Blume.